2006
DOI: 10.1007/s10533-006-9010-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of climate on average nitrogen export from large watersheds in the Northeastern United States

Abstract: The flux of nitrogen in large rivers in North America and Europe is well explained as a function of the net anthropogenic inputs of nitrogen to the landscape, with on average 20 to 25% of these inputs exported in rivers and 75 to 80% of the nitrogen retained or denitrified in the landscape. Here, we use data for average riverine nitrogen fluxes and anthropogenic inputs of nitrogen over a 6-year period (1988)(1989)(1990)(1991)(1992)(1993) for 16 major watersheds in the northeastern United States to examine if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
216
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(238 citation statements)
references
References 45 publications
18
216
4
Order By: Relevance
“…Chloride was assumed to be a conservative tracer for atmospheric deposition, such that the expected concentration of N ions in stream water was calculated from the product of the observed stream water chloride ion concentration and the ratio of atmospheric N flux to chloride flux. The ratio of observed to expected N ion concentrations in stream water yielded a minimum N retention of 82% or maximum export of 18% for the watershed, which is lower than the estimate of 26% N export for northeastern U.S. watersheds (Howarth et al, 2006) and higher than the estimate of 6% N export for North Carolina's Neuse River Estuary (Whitall et al, 2003 Figure 1) (Strayer et al, 2007). From the Gandy Bridge data, wet deposition rates were calculated according to eq 1, where C rain is the daily rainfall concentration of either NO 3 À -N or NH 4 þ -N and has units of mg L À1 , D is the rainfall depth and has units of cm d À1 , and F wet is the deposition rate (i.e., flux) and has units of kg N ha À1 d À1 .…”
Section: Nitrogen Export From the Watershedcontrasting
confidence: 57%
“…Chloride was assumed to be a conservative tracer for atmospheric deposition, such that the expected concentration of N ions in stream water was calculated from the product of the observed stream water chloride ion concentration and the ratio of atmospheric N flux to chloride flux. The ratio of observed to expected N ion concentrations in stream water yielded a minimum N retention of 82% or maximum export of 18% for the watershed, which is lower than the estimate of 26% N export for northeastern U.S. watersheds (Howarth et al, 2006) and higher than the estimate of 6% N export for North Carolina's Neuse River Estuary (Whitall et al, 2003 Figure 1) (Strayer et al, 2007). From the Gandy Bridge data, wet deposition rates were calculated according to eq 1, where C rain is the daily rainfall concentration of either NO 3 À -N or NH 4 þ -N and has units of mg L À1 , D is the rainfall depth and has units of cm d À1 , and F wet is the deposition rate (i.e., flux) and has units of kg N ha À1 d À1 .…”
Section: Nitrogen Export From the Watershedcontrasting
confidence: 57%
“…Ultimately, the fate of Nr that enters terrestrial systems appears to be under strong climatic control (25), an interaction that helps explain regional differences in N export and that should be considered in forecasts of future Ncycle dynamics. The fate and impacts of Nr are also often dependent on its chemical form, further highlighting the need to better resolve changing inputs of oxidized versus reduced forms of Nr.…”
Section: Vexing Questionsmentioning
confidence: 99%
“…By contrast, in the Seine, Scheldt and Mississippi river basins, a much higher fraction of NANI is delivered to the sea, causing severe marine eutrophication in the receiving coastal waters [23,24]. Although the processes responsible for the 'retention' of N along the N cascade are numerous and complex, Howarth et al [17,25,26] have shown that their overall effect in terms of the fraction of net total nitrogen inputs delivered to the sea is highly correlated to climate, varying between 100 per cent in cold and humid regions to less than 10 per cent under arid and warm climate conditions. Billen et al [14] have proposed a sigmoid relationship to represent the effect of specific run-off on the fraction of net total nitrogen input (NTNI ¼ NANI þ natural inputs) delivered to the sea (see the electronic supplementary material, figure S3).…”
Section: A Black Box Approach To Nitrogen Cycle Perturbation (A) Nitrmentioning
confidence: 99%